Sanksi Potong Tangan Bagi Pelaku Tindak Pidana Pencurian dalam Perspektif Hukum Islam - Mardani Mardani (Jurnal Hukum IUS QUIA IUSTUM, 2008)
Cutting hand penalty for theft cases, according to Muslim jurists’ view, is a maximum penalty, and hence, not all of such cases deserve for this mode of penalty. In case that the requirements for the implementation of such penalty cannot be found in a theft case, cutting hand may not be implemented and ta’zir shall apply instead. Ta’zir then, is considered as an educative penal system which falls under the authority of the judges to exercise their ijtihad capability.